Fundamentals of investments : valuation and management - Corrado, Charles J.; Jordan, Bradford D. (Boston : McGraw-Hill/Irwin, 2005)
Focuses on students as investment managers, giving them information to act on by placing theory and research in the proper context. This text offers consistent pedagogy, including a unified treatment of the four main types of financial investments: stocks, bonds, options, and futures.
Course resources included: Online learning center's premium content access card; stock-trak portfolio simulation.
Includes indexes.
rpm 15/08/2016
Keywords: Investments